Jogar e aprender: o jogo como possibilidade metodológica para o ensino de história do patrimônio cultural de Jaguariaíva-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This dissertation seeks to analyze possibilities for history teaching through the cultural heritage of the city of Jaguariaíva-PR for the early years of Elementary School, thereby contributing with referencial elements in the recognition of students' cultural identity, in a process of local memory rescue. Although there is literature on cultural heritage and heritage education in online repositories, most texts about Jaguariaíva are focused on other areas, such as Geography and Biology, and since Elementary School teachers are versatile with a generalist education, teaching subjects like Portuguese Language, Mathematics, Sciences, History, and Geography, they mostly lack specific training to work with local history content, potentially encountering difficulty in teaching about Jaguariaíva's cultural heritage. Therefore, this dissertation presents a board game as supportive educational material for teachers in the municipal education system. The text is divided into three chapters, the first discussing concepts related to cultural heritage and its importance in constructing cultural identity, the second addressing the city's history and cultural heritage through landmarks like the Sanctuary of Senhor Bom Jesus da Pedra Fria, Isabel Branco e Silva Square, Agent Durvalino de Azevedo Citizen Station, and the Matarazzo Reunited Factories Refrigerator, and the third chapter detailing the development of educational material as an integral part of the Professional Master's Program in History Teaching at the State University of Ponta Grossa, highlighting the use of games and digital technologies in history teaching.
Keywords: Patrimônio cultural; Ensino de história; Educação patrimonial; Jogos; Cultural heritage; History teaching; Heritage education; Games; CNPQ::CIENCIAS HUMANAS::HISTORIA